Assessment of the impact of climate change on Argan tree in the Mediterranean GIAHS site, Morocco: current and future distributions - Hakam, O.; Ongoma, V.; Beniaich, A.; Meskour, B.; Ait El Kadi, M.; Brouziyne, Youssef; Hssaisoune, M.; Tairi, A.; Labbaci, A.; Bouchaou, L. (Springer, 2024)
Climate change significantly challenges the sustainability of forest ecosystems, with broad socio-ecological impacts insufficiently assessed. This study examines one such critical system, the Globally Important Agricultural Heritage Systems (GIAHS), focusing on preserving the Argan tree in the Ait Souab-Ait Mansour region of southern Morocco. The region, including the Massa and Tamanart river basins, is crucial for Argan tree conservation, yet there is limited information on how climate change will affect the tree. This study aims to analyze climate variability trends and potential impacts on Argan tree distribution using observed (1983–2022) and projected rainfall and temperature data up to 2080. The MaxEnt model projected Argan tree distribution for 2041–2060 and 2061–2080 under four scenarios (SSP1-2.6, SSP2-4.5, SSP3-7.0, SSP5-8.5). Findings reveal significant climatic disparities, with warming of 0.4 °C between 1983 and 2022 and future temperatures reaching up to 4 °C between 2041 and 2080. Rainfall shows considerable variability, with a decrease of approximately 2.5 mm per decade during the rainy season. Projections indicate a decline in annual precipitation, impacting seasonality and increasing the frequency of extreme events during the argan fruit production season. Suitable areas for Argan trees are expected to decline, particularly in the Tamanart and Massa River basins. The study highlights a 47–65% reduction in highly adapted zones in the med term (2041–2060), and 49–81% in the long term (2061–2080), emphasizing the need for proactive adaptation measures in effort to conserve and increase Argan tree’s survival and productivity.